Isoflurane attenuates mouse microglial engulfment induced by lipopolysaccharide and interferon-γ possibly by inhibition of p38 mitogen-activated protein kinase. Issue 14 (28th September 2016) - Ryu, Jung-Hee; Wang, Zhi; Fan, Dan; Han, Sung-Hee; Do, Sang-Hwan; Zuo, Zhiyi
Abstract : Microglial engulfment is a basic function to clean up dead and injured cells and invaders, such as bacteria. This study was designed to assess the effects of isoflurane on the microglial engulfment induced by lipopolysaccharide (LPS) plus interferon-γ (IFN-γ) and the involvement of p38 mitogen-activated protein kinase (MAPK) in these effects. C8-B4 microglial cells were exposed to 1, 2, and 3% isoflurane at 2 h after the initiation of LPS (100 ng/ml) and IFN-γ (1 ng/ml) stimulation. Fluorescent immunostaining was performed to assess the percentage of cells with engulfment of fluorescent microspheres after stimulation for 24 h. P38 and phosphorylated p38 were determined by Western blotting. Isoflurane concentration dependently decreased microglial engulfment stimulated by LPS and IFN-γ. LPS and IFN-γ increased the phosphorylated p38 in microglial cells. This upregulation was decreased by isoflurane. SB203580, a p38 MAPK inhibitor, abolished the LPS-induced and IFN-γ-induced increase of engulfment activity, whereas anisomycin, a p38 MAPK activator, partly reversed the isoflurane-decreased microglial engulfment activity. These results suggest that isoflurane reduces LPS-induced and IFN-γ-induced microglial engulfment and that these effects may be mediated by inhibiting p38 MAPK.